Investigating the impact of flow rate ramp-up on carbon dioxide start-up injection. (September 2019) - Samuel, Revelation J.; Mahgerefteh, Haroun
Abstract: Carbon Capture and Storage (CCS) represents the technology for capturing carbon dioxide (CO2 ) produced from large emission sources, such as fossil-fuel power plants, transporting and depositing it in underground geological formations, such as depleted oil and gas fields. CO2 injection flow rate ramp-up time is essential for the development of optimal injection strategies and best-practice guidelines for the minimisation of the risks associated with the process. The rate of rapid quasi-adiabatic Joule-Thomson expansion when high pressure CO2 is injected into a low pressure injection well if not monitored carefully may lead to significant temperature drops posing several risks, including: blockage due to hydrate and ice formation with interstitial water. This paper employs a Homogeneous Equilibrium Mixture (HEM) model, where the mass, momentum, and energy conservation equations are considered for a mixture of liquid and gaseous phases assumed to be at thermal and mechanical equilibrium with one another. In particular, this study considers linearly ramped-up injection mass flow rate from 0 to 38.5 kg/s over 5 min (fast), 30 min (medium) and 2 h (slow). The reliability and applicability of the HEM model is tested against real CO2 injection experiment wellbore temperature data obtained from the Ketzin pilot site Brandenburg, Germany. The ramping up injection mass flow rate simulation results predicted the fast (5 min) injection ramp-up as best option for the minimisation of the associated process risks.